The effect of annealing on trapped copper oxides in particle-particle interfaces of cold-sprayed Cu coatings. (1st February 2022) - Tam, Jason; Yu, Bosco; Li, Weiwei; Poirier, Dominique; Legoux, Jean-Gabriel; Giallonardo, Jason D.; Howe, Jane; Erb, Uwe
Abstract: Cold-sprayed Cu coatings are known to have low ductility as the microstructure is composed of dynamically recrystallized fine grains, as well as larger crystals with high dislocation density. Annealing is typically employed to restore the ductility of the Cu coating to form larger crystals with low dislocation density; however, the influence of annealing on the microstructure and chemistry of the particle-particle interfaces (PPIs) have yet to be explored in great detail. Here, we report the structural evolution of PPI after annealing treatments. Nanoscale pores at the PPI can be effectively reduced by annealing and the trapped oxide films in the as-sprayed coatings break up and coarsen following classical interfacial phenomena. As a result, metallurgical bonding between particles increased significantly, contributing to the enhanced ductility of the cold-sprayed Cu coating. Graphical abstract: Image, graphical abstract